Classical notes on Gerard Manley Hopkins - West, S (Springer, 2006)
Hopkins does not parade his scholarship, but for much of his working life he was occupied in teaching classics, at various levels, and the importance of his classical studies for his poetry should not be underestimated. He could take for granted in a prospective reader a now unusual familiarity with the major classical authors; there is an increasing danger that we shall miss allusions that he could expect to seem obvious. His work needs to be seen against the background of the changing position of classics in his time. Whatever, had he lived longer, might have come of the various research projects mentioned in his correspondence, he was in advance of his time in his open-minded attitude regarding the influence on Greek civilization of the older cultures of the Near East. Notes on various poems to follow.